Pengembangan Strategi Belajar Flipped Classroom Untuk Meningkatkan Hasil Belajar Kognitif Siswa Pada Pelajaran Biologi Kelas XI MIPA SMAK Santo Fransiskus Assisi Samarinda - Bara, Marselina Oktavia; Rambitan, Vandalita M. M.; Boleng, Didimus Tanah (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2021)
The study was intended for: 1).to know the results of validation of Flipped Classroom learning strategy to improve the results of students' cognitive learning on XI grade in SMAK Santo Fransiskus Assisi Samarinda. 2). to know the effectiveness of the development of Flipped Classroom learning strategy to improve the results of students' cognitive learning on XI grade in SMAK Santo Fransiskus Assisi Samarinda. This development research refers to development measures with the model Thiagarajan & Semmel. The design of the development is grouped over 3 comprehensive development procedures: (a) define stages (definition) (b) design stages (design) and (c) development stages (development). The product's test consists of validation tests conducted by both study and linguistics specialists and product assessments conducted through the 2 stages the control class  test to 31 students of XI grade and experimental class testing to 31 students of XI grade in SMAK Santo Fransiskus Assisi Samarinda. Data collection uses interview,observation,questionnaire for linguists and test text instruments. The study (1) resulted in Flipped Classroom learning device (2) the product produced effectively improves the cognitive value of students of XI grade in SMAK Santo Fransiskus Assisi Samarinda as a study result,shown that the pretest average of 52.48 increased in a post test of 56.38 to the control class while 53.83 increased at the post test level of 87.37. And testing t independent t test of 0.467 > 0.05,this proves that there is no significant difference between control class and experiment class during learning using Flipped Classroom to improve students' cognitive learning on Biology of XI grade in SMAK Santo Fransiskus Assisi Samarinda.